A new large mound dwelling chiton (Mollusca), from the Late Ordovician Boda Limestone of central Sweden. (1st October 2020) - Högström, Anette E. S.; Ebbestad, Jan Ove R.; Suzuki, Yutaro
ABSTRACT: A new rare Upper Ordovician mound dwelling palaeoloricate chiton is described as Crassaplax collicola gen. et sp. nov. from three large isolated intermediate valves from the Katian carbonate mud mounds of the Boda Limestone in the Siljan district of central Sweden. Together with the previously known Spicuchelodes ? sp., also from the Boda Limestone, these are the only known Late Ordovician mound dwellers so far among the palaeoloricates, adding to Ordovician environments with reported chiton remains. Crassaplax collicola is distinguished from other Ordovician palaeoloricate chitons by their thick and large valves that can be 2 cm in length, and especially the clear differentiation between the lateral and central valve areas.